Warsaw Ghetto police : the Jewish Order Service during the Nazi occupation - Person, Katarzyna (Cornell University Press, 2021)
"Focuses on the history of the Jewish Order Service (known as the Jewish Police) in the Warsaw Ghetto, 1940-1943 and its perception among ghetto inhabitants"-- Provided by publisher.
"Published in association with the United States Holocaust Memorial Museum."
Translated from the Polish.
Keywords: Jüdischer Ordnungsdienst -- History.; Holocaust, Jewish (1939-1945) -- Poland -- Warsaw.; Jews -- Poland -- Warsaw -- History -- 20th century.; Getto warszawskie (Warsaw, Poland); Holocauste, 1939-1945 -- Pologne -- Varsovie.; Juifs -- Pologne -- Varsovie -- Histoire -- 20e siècle.; HISTORY / Jewish; Jews; Poland -- Warsaw; Poland -- Warsaw -- Getto warszawskie; 1900-1999; Jewish Police during the Holocaust, Jewish Order Service of the Warsaw Ghetto, Umschlagplatz, death camp of Treblinka.; History